2020
DOI: 10.3389/fimmu.2020.573200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Receptor Expression and Cytotoxicity of Human NK Cells and NK Cell Subsets in Overweight and Obese Humans

Abstract: Obesity is associated with an increased risk for several cancer types and an altered phenotype and functionality of natural killer (NK) cells. This study aimed to investigate the association of overweight and obesity with NK cell functions and receptor expression profiles in humans. Therefore, peripheral blood mononuclear cells were isolated from normal weight, overweight, and obese healthy blood donors. In depth analysis of immune cell populations and 23 different surface markers, including NK cell receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 106 publications
2
12
0
Order By: Relevance
“…Until now, only few data exist about the influence of obesity on underlying mechanisms of NK cells. Interestingly, recent studies on human NK cells indicate that the reduced cytotoxicity of NK cells in obese healthy blood donors is induced by an impaired death cell receptor-dependent killing pathway of NK cells (70). Future investigations, like in vivo killing experiments and detailed analyses of killing pathways are necessary to specify underlying mechanisms leading to the decreased NK cell cytotoxicity in obese mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only few data exist about the influence of obesity on underlying mechanisms of NK cells. Interestingly, recent studies on human NK cells indicate that the reduced cytotoxicity of NK cells in obese healthy blood donors is induced by an impaired death cell receptor-dependent killing pathway of NK cells (70). Future investigations, like in vivo killing experiments and detailed analyses of killing pathways are necessary to specify underlying mechanisms leading to the decreased NK cell cytotoxicity in obese mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that the expression level of the functional marker TRAIL and the activating NK receptor NKp46 are reduced in obese people [ 63 , 64 , 65 ]. In contrast, studies showed a highly activated NK cells in obese people with increased expression levels of CD69, and programmed cell death protein (PD)-1, as well as the inhibitory receptors of NKB1, CD158b, CD158i, NKG2A/CD94 complex, and Siglec-7 [ 60 , 61 , 63 , 65 ]. In addition, the expressions of CD16, and the adhesion molecule CD62L, and the maturation and differentiation marker CD27 on NK cells are downregulated in obese people [ 63 ].…”
Section: Lifestyles and Nk Cellsmentioning
confidence: 99%
“…In contrast, studies showed a highly activated NK cells in obese people with increased expression levels of CD69, and programmed cell death protein (PD)-1, as well as the inhibitory receptors of NKB1, CD158b, CD158i, NKG2A/CD94 complex, and Siglec-7 [ 60 , 61 , 63 , 65 ]. In addition, the expressions of CD16, and the adhesion molecule CD62L, and the maturation and differentiation marker CD27 on NK cells are downregulated in obese people [ 63 ]. Despite the enhanced activation, NK cells showed a decreased expression level of degranulating marker CD107a and decreased secretion of granzym B and perforin as well as the macrophage inflammatory protein (MIP)-1β in response to cancer cell lines in obese people [ 61 , 64 , 65 ].…”
Section: Lifestyles and Nk Cellsmentioning
confidence: 99%
See 2 more Smart Citations